EFEKTIVITAS KINERJA UNIT PELAKSANA TEKNIS (UPT) BINA LARAS DALAM REHABILITASI SOSIAL BAGI PENYANDANG DISABILITAS EKS PSIKOTIK DI PROVINSI RIAU - Andari, Sumi Oktavia; Meilani, Nur Laila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Increasing number of people with disabilities ex psychotic causes the increasing importance of social rehabilitation. In Riau Province social rehabilitation program has been done by UPT Bina Laras under the auspices of the Social Service of Riau Province. The purpose of social rehabilitation is for the recovery of people with disabilities ex psychotic in order to be able to return in the community. This study aims to determine the Effectiveness Performance of UPT Bina Laras in Social Rehabilitation for Disabled Persons Ex-Psikotik in Riau Province and to know the factors that influence the Performance Effectiveness of UPT Bina Laras in Social Rehabilitation for Disabled Persons Ex Psychotic in Riau Province.This study uses the concept of performance theory that Yazid (2009: 49) where the indicators used are quality of work, quantity of work, timeliness, work together, and responsibility. This study used descriptive qualitative method. Data were collected using interview technique, observation, and documentation. Data analysis with interactive model.Based on the results of this study, it can be seen that the implementation of social rehabilitation program implemented by UPT Bina Laras Riau Province has not run optimally. There are still obstacles in the implementation of social rehabilitation such as limited facilities and infrastructure and human resources. Therefore, it is necessary to improve the facilities and infrastructure in the implementation of social rehabilitation activities for people with disabilities ex psychotic and human resources such as doctors and psychologists who should stand-by from within the UPT Bina Laras. Keywords: Performance effectiveness, Social Rehabilitation, Ex Psychotic Disability